The Earliest Europeans : a Year in the Life: Survival Strategies in the Lower Palaeolithic - Hosfield, Robert (Oxbow Books, 2020)
The Earliest Europeans explores the early origins of man in Europe through the perspective of 'a year in the life': how hominins in the Lower Palaeolithic coped with the year-round practical challenges of mid-latitude Europe with its distinctive temperatures, seasonality patterns, and available resources. Current research has provided increasingly robust archaeological and Quaternary Science records, but there are ongoing uncertainties as to both the earliest Europeans' specific survival strategies and behaviours, and the character of their dispersals into Europe. In short, how sustained and 'successful' were the individual phases of European occupation by Lower Palaeolithic hominins and what sorts of 'human' where they?